2019
DOI: 10.1503/cmaj.181712
|View full text |Cite
|
Sign up to set email alerts
|

Combined impacts of multimorbidity and mental disorders on frequent emergency department visits: a retrospective cohort study in Quebec, Canada

Abstract: ultimorbidity, the co-occurrence of multiple chronic illnesses, has increased in prevalence as populations age and improved medical treatment extends the lives of patients with chronic illness. 1,2 Mental disorders affect as many as 30% of people with multimorbidity. 1 Mental disorders are also associated with more severe physical illness, including increased symptom burden, shortened lifespan and compounded disability. 3,4 Both physical multimorbidity and mental disorders are growing individual and public-hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 39 publications
(42 reference statements)
2
45
0
Order By: Relevance
“…Only a very small proportion of people with CMDs (c. 3%) in our sample had received specialist psychiatric care, implying less severe symptomatology overall, yet their physical health compared with that of the general population was poor and even comparable with that of people with SMI. The chronic nature and the multiple pastyear physical conditions present in a large proportion of people with CMDs are also indicative of the high rates of active physical multimorbidity, in line with previous findings elsewhere [15][16][17].…”
Section: Interpretation Of Findings and Comparison With Other Studiessupporting
confidence: 86%
See 2 more Smart Citations
“…Only a very small proportion of people with CMDs (c. 3%) in our sample had received specialist psychiatric care, implying less severe symptomatology overall, yet their physical health compared with that of the general population was poor and even comparable with that of people with SMI. The chronic nature and the multiple pastyear physical conditions present in a large proportion of people with CMDs are also indicative of the high rates of active physical multimorbidity, in line with previous findings elsewhere [15][16][17].…”
Section: Interpretation Of Findings and Comparison With Other Studiessupporting
confidence: 86%
“…Despite being mostly treated in primary care, people with CMDs also have a very complex association with physical disorders acting in a multifaceted and bidirectional pathway that increases disability and health resources [13,14]. Previous studies have consistently demonstrated elevated risks of physical comorbidity among people with CMDs compared with the general population [15,16], predisposing to even worse outcomes than having either illness alone [13,17]. Additionally, the prevalence of unhealthy lifestyle behaviors among people with CMDs may be comparable to those observed in people with SMI in some instances [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being less advantaged socioeconomically accelerates the process, so in deprived areas multimorbidity occurs earlier in life 3. Children or young adults with serious congenital or acquired impairments often have multiple physical or mental illnesses,4 and the interaction between mental and physical health makes each harder to treat 5. Certain periods of life, including pregnancy, increase the probability that multiple conditions will present simultaneously.…”
mentioning
confidence: 99%
“…In a linked study, Gaulin and colleagues used logistic regres sion modelling to show synergistic effects of comorbid mental and physical illnesses on frequent visits to the emergency department (defined as ≥ 3/yr) across the province of Quebec. 3 That is, the combination of the 2 types of disorders was associ ated with more visits than would be expected if one assumed a simple additive effect. Specifically, the researchers found that synergy between mental and physical disorders accounted for 13%-24% of emergency department visits in those with mental disorders.…”
mentioning
confidence: 98%